Controls of Slab Subduction and Tearing on the Magmatism of Wrangell Volcanoes in South‐Central Alaska - Meng Liu; Haiying Gao (Geophysical Research Letters)
Abstract This study integrates data from all broadband seismic stations in Alaska and northwestern Canada in 1999–2022 to construct a shear‐wave velocity model for south‐central Alaska and northwesternmost Canada, using ambient noise wave propagation simulation and inversion. Our model reveals three key features, including (a) the presence of the subducting Yakutat slab with apparent velocity reductions near the trench and within its flat segment, (b) two slab segments beneath the Wrangell volcanic field, differing in steepness, depth, and seismic velocity, and aligning spatially with the northwestern and southeastern volcano clusters, and (c) the existence of slab windows between the Yakutat and Wrangell slabs and between the northwestern and southeastern portions of the Wrangell slab. Our findings reinforce that the Wrangell volcanoes are predominantly influenced by subduction‐related magmatism. Furthermore, the two slab windows could have induced asthenospheric upwelling, contributing to the volcanism in the Wrangell clustered volcanoes.